Non-Custodial Sentences in Light of Penal Policy 1970-1998 (Archives of Criminology, 2002)
The subject of the article is an analysis of the non-custodial sentencje known in Poland as curtailment of liberty (and thus excluding fines) as an important instrument of penal policy in the 1970-1998, the main focus being on two strands or this policy–legislative policy and penal policy–to the exclusion of the latter’s administrative aspects.In the light of the guiding principles of the 1969 Criminal Code non-custodial sentences were intended to become an important penal policy measure for treatment of perpetrators of  minor offenses and at the same time to provide a substitute for short terms of imprisonment, which had been found relatively ineffective as a means of achieving rehabilitation of convicted offenders. However, the normative extent of the code’s provision for non-custodial penalties proved to be relatively narrow. Within the range of alternatives to custodial punishment curtailment of liberty was an option available only under 17.5% of the defined offenses. Under Article 54 §1 sentencing to curtailment of liberty was admissible for 24% of all offenses and under Article  57 §1.3 for 27.9% of the total. The potential possibilities of non-custodial treatment of offenders were circumscribed by the provisions of Articles 54 §2, 52, 59 and 60.      A significant influence on the frequency of sentencing to curtailment of liberty was the actual incidence of criminal acts punishable by alternative form of treatment. Based on an analysis of Ministry of Justice and judicial statistics it appears that such acts were not among the most frequently committed offenses, amounting to about 10% of all convictions. The systematic growth of the proportion of sentences to curtailment of liberty, from 6.2% in 1970 to l8% in 1980, should, therefore, be regarded as achievement of the maximum level of possible sentences of this kind. If we consider the share of curtailment of liberty in the structure of sentences for offenses punishable by alternative forms of treatment we will find that there was a judicial bias towards curtailment of liberty. The frequency of such treatment of offenders fluctuated between 32.83% and 56.54%, while the range for fines came to 21.26%‒5I,99 % and for imprisonment to 3,4%‒21.26%. It can, therefore, be said that in the first decade following the 1969 Criminal Code’s entry into force curtailment of liberty fulfilled the purpose envisaged by the lawmakers, that is as an alternative to short terms of imprisonment. Undoubtedly, a factor contributing to the increase in the proportion of non-custodial sentences in the structure of final and conclusive judgments was the jurisprudence of the Supreme Court, in particular its guidelines for the administration of justice and judicial practice issued on 30 May 1979 (VII KZP 31/1977) concerning sentencing policy with respect to offenses for which the prescribed punishment is, interchangeably, imprisonmet, curtailment of liberty or a fine. Imprisonment, these stated, should be a penalty imposed only in the last resort when non-custodial forms of treatment are deemed incapable of performing the function of protection of the legal order.       If a salient characteristic of the 1970s was stability of legislative policy, which  precluded the possibility of shaping penal policy by means of legislation, the 1980s, or more precisely the period from 12 December 1981 to 1989, saw the emergence of a tendency in the opposite direction. For it brought the adoption of numerous basic amendments in criminal legislation, the general thrust of which was towards severer difinition of criminal responsibility. This was reflected in a decrease in the proportion of non-custodial sentences in the structure of final and conclusive judgments (from 15.6% in 1981 to 8.2% in 1984) and a concurrent increase in the frequency with which courts sentenced offenders to imprisonment (from 25.3% in 1981 to 33.1% in 1984).        During the years in which the rigorous provisions of the Special Criminal Responsibility Act were in force, that is in the period from 10 May 1985 to 30 June 1988, there was a systematic rise in the proportion of curtailment of liberty in the structure of sentences (from 10.1% in 1985 to 17.4% in 1987), which might have something to do with the introduction by the May legislation of provisions allowing for non-custodial treatment of offenders in summary proceedings.       The 1988 amendments to the Criminal Code, aimed at relaxing definitions of criminal responsibility, included, albeit in only a limited degree, provisions relating to the applicability of curtailment of liberty. These changes reflected a desire to increase the significance of non-custodial treatment in penal policy. However, in judicial practice there ensued a decrease in sentencing to curtailment of liberty, from 10.5% in 1989 to 5.3% in 1990.       The period of political, economic and social change in Poland which began  in 1989 stimulated criminal law reform. The aim of numerous legislative change which followed was to reduce the punitive  character of the Criminal Code. One reflection of this was greater provision for non-custodial treatment of offenders (introduced by the new Criminal Code enacted in 1995) through a broadening of the grounds for commuting sentences of imprisonment to curtailment of liberty or a fine under Article 54), reduction of the role of repeated criminality as an aggravating circumstance in punishment of offenders, and abolition of extended sentences for offenses classified as "hooligansm" or committed by repeat offenders.       In 1991-1995 the share of curtailment of liberty in the structure of sentences held steady at a level of 3.5%‒3,9%, making it the lowest ever for the period in which the 1969 Criminal Code was in force. This was not a result of the greater repressiveness of the criminal justice system since we observed a drop in the frquency of sentences of imprisonment. The courts tended to favor the use of conditional suspension of custodial sentences (the share of which rose from 43.9% in 1989 to 55.1% in 1997) and fines (up from 4.9% in 1989 to 27.4% in 1997). The explanation should, rather, be sought in problems with execution of sentences to curtaiment of liberty, chief among them the job shrinkages caused by changes in the free-market economy.      Analysis indicates that curtailment of liberty did not fulfill the expectations associated with this form of punishment. It did not become a significant instrument of penal policy nor did it contribute to reducing the scale of sentencing to terms of imprisonment. Even after a substantial widening of provision for punishment by curtailment of liberty its share of sentences ordered by the courts reached a level of only 5.2% (in 1977).      The new Criminal Code has substantially expanded the possibilities of sentencing offenders to curtailment of liberty. This form of punishment is intended to be an important instrument of penal policy with respect to misdemeanors and minor offenses and to replace imprisonment and even fines if ordering the latter is thought to serve no purpose. At the same time the Criminal Code has introduced modifications in the legal shape of this punishment. By preserving, contrary to the intentions of the code’s original drafters, multivariate forms of punishment it gives curtailment of liberty some of the hallmarks of probation by introducing the possibility of imposing certain additional conditions and establishing supervision. The new elements in the design of curtailment of liberty have met with numerous criticisms of the doctrine (including by the authors of the article). How it will affect the functioning of the institution analyzed the immediate future will tell.